2021
DOI: 10.1074/jbc.ra120.015152
|View full text |Cite
|
Sign up to set email alerts
|

Genome editing demonstrates that the −5 kb Nanog enhancer regulates Nanog expression by modulating RNAPII initiation and/or recruitment

Abstract: Transcriptional enhancers have been defined by their ability to operate independent of distance and orientation in plasmidbased reporter assays of gene expression. At present, histone marks are used to identify and define enhancers but do not consider the endogenous role of an enhancer in the context of native chromatin. We employed a combination of genomic editing, single cell analyses, and sequencing approaches to investigate a Nanog-associated cis-regulatory element, which has been reported by others to be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Some authors consider enhancers combinations of multiple DHSs or longer stretches of DNA sequences. However, other studies have shown that the activity of these long enhancers can be reproduced by shorter versions of ~500 bp [40,41]. Coordinates of all tested genomic fragments are provided in Supplementary Dataset 1.…”
Section: Experimental Designmentioning
confidence: 99%
“…Some authors consider enhancers combinations of multiple DHSs or longer stretches of DNA sequences. However, other studies have shown that the activity of these long enhancers can be reproduced by shorter versions of ~500 bp [40,41]. Coordinates of all tested genomic fragments are provided in Supplementary Dataset 1.…”
Section: Experimental Designmentioning
confidence: 99%
“…The master pluripotency TF Nanog is near three SEs (−5SE, −45SE, +60SE, named based on distance from Nanog promoter in kb; Figure 1A; Pulakanti et al, 2013;Whyte et al, 2013;Blinka et al, 2016;Agrawal et al, 2021). These SEs and the numerous CTCF sites at the locus make it an ideal model system to understand how CREs regulate cell fate decisions by modulating Nanog expression (Blinka and Rao, 2017).…”
Section: Enhancersmentioning
confidence: 99%
“…Circular Chromosome Capture (3C) of the three SEs at the Nanog locus demonstrates that they physically interact with the Nanog promoter, but CRISPR-based deletion of each SE differentially alters expression (Blinka et al, 2016). Deletion of the −45SE causes an approximately 50% decrease in Nanog expression, deletion of the −5SE causes a nearly 90% decrease, but deletion of the +60SE causes no change (Figure 1B; Blinka et al, 2016;Agrawal et al, 2021). This leads to the important question: through what mechanism(s) do the −5SE and −45SE regulate Nanog, expression?…”
Section: Enhancersmentioning
confidence: 99%
See 2 more Smart Citations